Capital Fulfillment Strategy For Trigona Honey Bee Smes In Balangan Sembung Village, Mengwi District, Badung Regency - Ni Made Rustini; I Ketut Selamet; A. A. Sri Purnami (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2023)
Bali has started to develop honey bee cultivation of the stingless bee type. The type of honey bee that is widely cultivated by the people of Bali is the Trigona laevicep species known as